Faktor Fisik dan Non Fisik yang Memengaruhi Aksesibilitas secara Perseptual dan Aktual terhadap Taman Monas, Jakarta - Nadhira Putri Rizkia; Rulli Pratiwi Setiawan (TATALOKA, 2021)
Monas park as the biggest urban park in Jakarta has various social, economic, and environmental benefits for its visitors. These benefits can be acquired if the park is accessible to the community. Previous research found that there are differences between visitor perception and the actual measured distances, where visitor perception is more important than measured distance. In addition, benefits gained by visitors can be more valuable than the accessibility cost of a park. This shows that if a park can provide benefits to the visitors, the visitors will not consider the accessibility cost as a burden. This research aims to find the factors affecting the visitors’ accessibility to Monas Park, in which the accessibility is measured based on perceptual and actual. This research involved active visitors who live in the Greater Jakarta area. The data were analyzed using Structural Equation Modelling Partial Least Square (SEM PLS) to find the factors affecting both perceptual and actual accessibilities. The results showed that security, transportation, and personal aspects affect perceptual accessibility, while park facilities and personal aspects affect the actual accessibility. Besides the physical factors, the non-physical factor such as leisure time availability also affects the perceptual and actual accessibilities to Monas Park.